From reels to real gold: The interplay of ease, social influence, and risk perception in Gen Z's digital gold adoption - Rachmaniar Myrianda Dwiputri; Dwi Adi Prakoso (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The increasing availability of digital financial services has encouraged greater participation by Generation Z in investment activities, including digital gold. Although prior technology adoption studies have highlighted the importance of effort expectancy and social influence, limited attention has been given to the role of perceived risk in shaping adoption decisions within asset-backed digital investment environments. Methods: This study investigated the behavioral intention of Generation Z to use the Pegadaian digital gold application. Data were collected from 113 users in the Greater Jakarta area and analyzed using Structural Equation Modeling to evaluate both direct and moderating relationships among the proposed variables. Findings: The analysis revealed that effort expectancy positively influenced behavioral intention (β = 0.425, p <0.001), while social influence exerts a stronger effect (β = 0.629, p <0.001). Perceived risk weakened the positive association between effort expectancy and behavioral intention (p <0.05), In contrast, its interaction with social influence was not statistically significant. These results indicate that social influence remains a robust driver of adoption decisions even when risk concerns are present. Conclusion: The intention to adopt digital gold among Generation Z is shaped by technological and social considerations, whereas perceived risk exerts a conditional influence. Novelty/Originality: By examining perceived risk as a contextual moderator rather than a direct predictor, this study offers additional evidence on how psychological evaluations influence digital investment adoption and enriches the application of UTAUT2 in asset-backed fintech services.